Pursuit of Digital Innovation in Psychiatric Data Handling Practices in Ireland: Comprehensive Case Study - Rana Zeeshan; John Bogue; Amna Gill; Mamoona Naveed Asghar (JMIR Human Factors)
Abstract BackgroundIreland is ranked among the most disadvantageous European countries in terms of mental health challenges. Contrary to general health services that primarily focus on diagnosis and treatment, the mental health sector in Ireland deals with highly sensitive psychiatric case notes based on patient-doctor conversations. Such data, therefore, must be collected, analyzed, and stored with an approach customized specifically for psychiatry. ObjectiveThis study’s objective involves examining the state of data handling practices in the Irish Mental Health Services (MHS), identifying the shortcomings regarding privacy, security, and usability of psychiatric case notes, and proposing an innovative technological solution that addresses most of the surfaced challenges. MethodsThe study was conducted using a comprehensive methodology. Our approach involved a thorough literature review, ethics approval, web-based surveys with mental health professionals as participants, interviews of psychiatrists, interactions with mental health organizations, analysis of inspection reports by the Ireland Mental Health Commission, and comparative evaluation of existing IT solutions. The thoroughness of our adopted research methodology instills confidence in the reliability and validity of our findings. ResultsOur study revealed outdated data management, heavy reliance on paperwork resulting in serious repercussions, parallel workload, alarmingly low readability of notes, and a nonviable setup that hinders research and analytical examination. Our survey reported an average score of 4.37 of 10 (SD 1.25) given by participants in terms of technology use. Regarding privacy measures, 75% (n=12) of participants mentioned that staff members are allowed to keep their phones while accessing psychiatric case notes. Similarly, 80% (n=13) of submissions highlighted that multiple staff members can access sensitive notes and patients’ contact information. On the other hand, Mental Health Commission reports showed that their inspections are limited to evaluating physical privacy only. Regarding technological comparative analysis, we observed that conventional IT solutions are vulnerable against cyberattacks and fall short in addressing multiple challenges simultaneously. Therefore, an innovative convergence of different technologies is needed. Our research supports speech-to-text transcription for data collection, interactive artificial intelligence for data analysis, and permissioned blockchain for data storage and retrieval. Our survey participants also estimated the proposed solution to optimize their workload by an average of 35%.